THE INFLUENCE OF SALT INTAKE ON THE COURSE OF EXPERIMENTAL TOXOPLASMOSIS IN OUTBRED OR INBRED MOUSE STRAINS - Bruno Silva de Oliveira, Claudio; da Silva Rodrigues Meurer, Ywlliane; Santana de Sena Pereira, Valeska; Maria de Araújo Andrade, Joelma; Tavares, Juliete; Ferreira de Andrade Neto, Valter (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
Many environmental factors contribute to an effective immune response against Toxoplasma gondii (Tg) infection, among which diet is important in triggering the immune response of the host to infection. Emerging reports suggest that salt intake undermines the regulatory mechanisms mediated by innate and adaptive immune cells. Unfortunately, the impact of an Intermediate Salt Diet (ISD) on the pathogenesis and immune response to toxoplasmosis remains unclear. The purpose of this study was to evaluate the susceptibility profile to an ISD (NaCl 2%) of two mouse strains (outbred Swiss and inbred C57BL6) infected by the ME49 strain of Tg. Our data confirm an antagonistic susceptibility to oral Tg infection among the two mouse strains. Sodium intake induced the highest mortality in C57BL6 compared to Swiss mice in the infected groups. A simultaneous ISD with the infection did not induce significant differences in body weight in either mouse strains. Both mouse strains showed an antagonistic response to a sodium intake diet on the number of parasite brain cysts. An increased number of brain cysts in C57BL6 ISD-Tg animals were noted while Swiss ISD-Tg animals presented a decrease in the number of brain cysts compared to NSD-Tg (Normal Salt Diet) for both mouse strains. Furthermore, sodium intake caused a significant reduction in the specific humoral immune response against Tg in inbred C57BL6 mice. Thus, our data reveal that an ISD affects the humoral immune response in the murine model and influences the course of Tg infection.